Mind the absent gap: Gender-specific competitiveness in non-professional sports - Anna Katharina Pikos; Alexander Straub (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2019)
There is wide evidence for gender differences in competitiveness and performance under pressure from experimental economics and single-sex professional sports. We analyze these differences in a sport with direct gender competition. Our unique data consists of over 500,000 observations from around 11,000 German ninepin bowling games of which around 15% are from mixed-gender leagues. Men perform better against women on average but this is fully explained by differences in ability. Our results are robust to instrumenting for opposite gender using the sex composition of the opponent team. Surprisingly, gender differences in tight situations do not seem to play a role.
Keywords: J16; D90; Z22; 330; gender; gender competition; sports economics